The experimental determination of hydromagnesite precipitation rates at 22.5–75ºC. (November 2014) - U.-N. Berninger,; Jordan, G.; Schott, J.; Oelkers, E. H.
Abstract : Natural hydromagnesite (Mg5 (CO3 )4 (OH)2 ·4H2 O) dissolution and precipitation experiments were performed in closed-system reactors as a function of temperature from 22.5 to 75ºC and at 8.6 < pH < 10.7. The equilibrium constants for the reaction Mg5 (CO3 )4(OH)2 ·4H2 O + 6H + = 5Mg2+ + 4HCO3 – + 6H2 O were determined by bracketing the final fluid compositions obtained from the dissolution and precipitation experiments. The resulting constants were found to be 1033.7±0.9, 1030.5±0.5 and 1026.5±0.5 at 22.5, 50 and 75ºC, respectively. Whereas dissolution rates were too fast to be determined from the experiments, precipitation rates were slower and quantified. The resulting BET surface areanormalized hydromagnesite precipitation rates increase by a factor of 2 with pH decreasing from 10.7 to 8.6. Measured rates are approximately two orders of magnitude faster than corresponding forsterite dissolution rates, suggesting that the overall rates of the low-temperature carbonation of olivine are controlled by the relatively sluggish dissolution of the magnesium silicate mineral.